ANALISIS SENTIMEN MEDIA SOSIAL TIKTOK DENGAN METODE SUPERVISED LEARNING PADA ALGORITMA MACHINE LEARNING - Nur Az-zahra, Rizka Namira; Fitrialdi, Moh Rizqi; Nurjanah, Esa; Darmawan, Mardotilah; Firmansyah, Ricky (TI S1 FKOM UNIKU, 2021)
TikTok is an application that is downloaded by many people nowadays, it is because the government policy pushes us to stay at home during this pandemic COVID-19. There are many content creators who made up their creative ideas on TikTok and also the netizens who watch them are entertained. Certainly, TikTok cannot be separated by a thing that is called hashtag. By using hashtag(s), the similar contents can be classified easily. Even the content can be added to FYP (For Your Page). If it is added to FYP, the content can go viral instantly. Of course, there are many pros and cons on the viral content. Sentiment analysist is a study of public judgement and opinion. This study uses Machine Learning method. It is a supervised learning on sentiment analysist of a video that is currently going viral, which is on that video there are positive, negative, and neutral opinion.